Does Internal Marketing Influence Employee Loyalty? Evidence From the Ghanaian Banking Industry - Narteh, B.; Odoom, R. (Services Marketing Quarterly, 2015)
Even though internal marketing has been a buzzword for over 25 years now, most of the literature has largely remained theoretical and few empirical studies, especially in sub-Saharan Africa, exist. Moreover, the relationship between internal marketing and employee loyalty has been underresearched. The current study explores the relationship between internal communication, reward systems, empowerment, organizational culture, training, and organizational commitment and their relationship with employee loyalty using 248 retail bank staff members. The results indicate that the internal marketing dimensions, with the exception of organizational culture, are significantly associated with employee loyalty. Managerial implications are also discussed. © 2015, Copyright © Taylor & Francis Group, LLC.
Keywords: employee loyalty; Ghana; internal marketing; retail banking